KOMUNIKASI INTERPERSONAL DALAM MENINGKATKAN KESADARAN MASYARAKAT AKAN FASILITAS DAN KEBERSIHAN DI DESA TANJUNG ALI JEJAWI OGAN KOMERING ILIR - Marleni, Marleni; Austin, Trecy; Bayumi, Ruli Ihsan (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2022)
This community service is to provide knowledge related to communication within the Tanjung Ali Jejawi OKI Village community which is part of the activities provided periodically every year. Tanjung Ali Jejawi OKI Village still experiences a lack of public awareness of the cleanliness of the surrounding environment and there are no barriers between hamlets. In Tanjung Ali Jejawi OKI Village, the community is still not aware of environmental cleanliness, especially in the mosque area where people perform prayers and other religious activities. still don't know the boundaries of the hamlet, where there is a sign that connects the hamlet, providing cleaning equipment, the importance of creating a healthy and clean environment and together with the community, making the boundaries of each hamlet in Tanjung Ali Village. This community service aims to provide knowledge to the community about the importance of environmental cleanliness and to be able to inform the Hamlet community about the boundaries between the Hamlet and the community.